PENGARUH NAUNGAN DAN BERBAGAI MEDIA TANAM TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SELADA (Lactuca sativa L.) - Yulinda Tanari; Vera Vita (Agropet, 2017)
The objective of this research is to find out the influence of shield and some planting medium toward the growth and production of lettuce plant. This research uses split plot design with 3 times repetition. The treatment consists of 2 main compartments and 6 sub compartments. The main compartment is a shield that consists of two levels  which are N1 (0% shield) and N2 (50% shield). Sub compartment is a growth media this consists of six levels which are M0 (soil), M1 (soil + sand 1:1), M2 (soil + charcoal 1:1), M3 (soil + chickenrun 1:1), M4 (Soil + goat stall fertilizer 1:1), M5 (Soil + cow hause fertilizer 1:1). The abserved parameter are temperature and humidity, plant height, leaf number, leaf wide, wet weight of the plant, wet weight of tree, wet weight of root, dry weight of plant, dry weight of tree, and dry weight of root. The research result shows that the combination of 0% shield and planting medium + chickenrun fertilizer has significant influence toward all the production component of the plant. Key Words: Chickenrun, Cow Hause Fertilizer and Husk Charcoal